Energy absorption characteristics of polyurethane composite foam filled tubes subjected to quasi-static axial loading - Subramaniyan, S Kanna; Mahzan, Shahruddin; Ghazali, Mohd Imran; Ahmad Zaidi, Ahmad Mujahid; Prabagaran, Prasath Kesavan (Trans Tech Publications, 2013)
Foam-filled enclosures are very common in structural crashworthiness to increase energy absorption. However, very less research has been targeted on potential use of natural/recycled material reinforced foam-filled tubes. Therefore, an experimental investigation was performed to quantify energy absorption capacity of polyurethane (PU) composite foam-filled circular steel tubes under quasi-static axial loading. The thickness of the tubes was varied from 1.9, 2.9 and 3.6 mm. The tubes were filled with PU composite foam. The PU composite foam was processed with addition of kenaf plant fiber and recycled rubber particles that were refined at 80 mesh particulates into PU system. The density of PU resin was varied from 100, 200 and 300 kgm-3 . The PU composite foam-filled tubes were crushed axially at constant speed in a universal testing machine and their energy absorption was characterized from the resulting load-deflection data. Results indicate that PU composite foam-filled tubes exhibited better energy absorption capacity than those PU foam-filled tubes and its respective empty tubes. Interaction effect between the tube and the foam and incorporation of filler into PU system led to an increase in mean crushing load compared to that of the unfilled PU foam or tube itself. Relatively, progressively collapse modes were observed for all tested tubes. Findings suggested that composite foam-filled tubes could be used as crashworthy member.